The Future of Autonomous Vehicles: Ethical Implications (Journal of responsible AI & ethics, 2026)
Autonomous vehicles (AVs) are rapidly progressing from concept to reality, with the potential to revolutionize transportation systems worldwide. However, alongside the technological advancements, the introduction of AVs raises critical ethical questions that must be addressed before their widespread adoption. These ethical concerns revolve around issues such as decision-making in life-or-death situations, privacy, data security, accountability, and the social impact of transitioning to an AV-driven society. This paper explores the ethical implications of autonomous vehicles, examining the challenges and opportunities they present for both individuals and society as a whole. By drawing on existing literature, case studies, and expert opinions, the paper investigates the moral dilemmas associated with AV technologies and their integration into existing legal, social, and economic frameworks. The paper also highlights the responsibility of manufacturers, policymakers, and society in ensuring that the deployment of AVs aligns with ethical principles and promotes public trust. Recommendations for ethical frameworks, future research directions, and regulatory approaches are provided to guide the development of AVs in a manner that respects human rights, equity, and safety.